Psychological Factors Affecting on Developing Reading Skills and Evaluation of Reading Strategy Knowledge - Wathiq Al – Husseini1, Asst. Prof. Dr. Diaa Oued Al Arnousi1, Qassim Raheem1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The questions are one of the most common and used methods in the educational process and in schools all over the world and are the most important educational strategies. Because questions are a great place in teaching, which is the mainstay of the dialogue method and is like the driving force in the lesson. The educators say (If you want to become a highly competent educator, it is important that you begin to apply and develop educational questions). These questions also occupy great importance in the educational process after which the standard means of knowing the readiness of the students and the level of information they received, in a good question, we achieve the desired goal and achieve a desirable educational product. Besides , the exams are a means to help educators to make different educational decisions, so that , there have been wide concerns calling for the reform of the test questions and the evidence of that conferences that discussed this problem, studies and research aimed at diagnosing them in order to address, improve and develop their defects to achieve best results in education.